Protective Effects of Lentinan Against Lipopolysaccharide-Induced Mastitis in Mice - Huifang Yin; Huifang Yin; Huifang Yin; Guanhong Xue; Ailing Dai; Ailing Dai; Ailing Dai; Haichong Wu; Haichong Wu; Haichong Wu (Frontiers Media S.A., 2021)
Mastitis is a worldwide production disease in dairy cows, which mainly affects milk yield, causing huge economic losses to dairy farmers. Lentinan is a kind of polysaccharide extracted from Lentinus edodes, which has no toxicity and possesses various pharmacological activities including antibacterial and immunomodulatory effects. Therefore, the anti-inflammatory function of lentinan on LPS-stimulated mastitis was carried out, and the mechanism involved was explored. In vivo, lentinan greatly reduced LPS-stimulated pathological injury, myeloperoxidase (MPO) activity, and the proinflammatory factor production (TNF-α and IL-1β) in mice. Further study was performed to determine the activation of the Wnt/β-catenin pathway during LPS stimulation. These results suggested that LPS-induced activation of the Wnt/β-catenin pathway was suppressed by lentinan administration. In vitro, we observed that the mouse mammary epithelial cell (mMEC) viability was not affected by lentinan treatment. As expected, LPS increased the TNF-α and IL-1β protein secretion and the activation of the Wnt/β-catenin pathway that was inhibited by lentinan administration in a dose-dependent manner in mMECs. Conclusively, lentinan exerts the anti-inflammatory function in LPS-stimulated mastitis via inhibiting the activation of the Wnt/β-catenin pathway. Thus, the results of our study also gave an insight that lentinan may serve as a potential treatment for mastitis.